You have the following equation given in the exercise:
![(1)/(3)y=6(x-(1)/(6))](https://img.qammunity.org/2023/formulas/mathematics/college/eq6vqkc7mbikw4dgeqrd6jjwv3xf7et1eu.png)
In order to solve for "y" in terms of "x", you can follow the steps shown below:
1. Apply the Distributive property, which states:
![\begin{gathered} a(b+c)=ab+ac \\ a(b-c)=ab-ac \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/p4etjt8mmqu3dw5t3iyrufhwzyzoy5w8bt.png)
Then:
![\begin{gathered} (1)/(3)y=(6)(x)-(6)((1)/(6)) \\ \\ (1)/(3)y=6x-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/wm0jkxdkc7jxi57nbs0yusqfm95i9hk7qy.png)
2. Now you must apply the Multiplication property of equality by multiplying both sides of the equation by 3:
![\begin{gathered} ((1)/(3)y)(3)=(6x-1)(3) \\ \\ y=18x-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/wkd71nu035eetn6xxno1nfkey7rcgglosz.png)
Therefore, the equation solved for "y" in terms of "x", is:
![y=18x-3](https://img.qammunity.org/2023/formulas/mathematics/college/u4kvomvlhtocrt6sdniu79jnvzidu2yojk.png)